1992
DOI: 10.1016/0014-5793(92)80640-3
|View full text |Cite
|
Sign up to set email alerts
|

A possible role for cysteine residues in the fidelity of DNA synthesis exhibited by the reverse transcriptases of human immunodeficiency viruses type 1 and type 2

Abstract: HIV reverse transcrlptases (RTs) have few cysteine residues rda t.ive to other RTs and retain their DNA polymerization functions followin8 eheJ~),ieal modification by thiol.speeifie reagents. The functional role or ire cysteines in the fidelity of the DNA-dependent DNA synthesis of HIV RTs has been addressed by chemical modification of the wild-type enzy:.~es in combination with the analysis of an ermymatically active mutant HIV-I RT in which all eysteines were modified to serines. We have observed an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
(16 reference statements)
1
14
0
Order By: Relevance
“…Parallel studies of the Klenow fragment of E. coli DNA polymerase I have revealed that the substitution of Tyr-766 leads to a substantial decrease in fidelity [29]. Reduced fidelity of DNA synthesis has also been observed with HIV-1 RT mutants in which Cys-38 and Cys-280 were replaced by serines [19]. It should be emphasized that all of the above-mentioned mutations result in a decrease in fidelity, while the mutant M184L and Y183F of HIV-1 RT show the opposite --an increase in fidelity.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Parallel studies of the Klenow fragment of E. coli DNA polymerase I have revealed that the substitution of Tyr-766 leads to a substantial decrease in fidelity [29]. Reduced fidelity of DNA synthesis has also been observed with HIV-1 RT mutants in which Cys-38 and Cys-280 were replaced by serines [19]. It should be emphasized that all of the above-mentioned mutations result in a decrease in fidelity, while the mutant M184L and Y183F of HIV-1 RT show the opposite --an increase in fidelity.…”
Section: Discussionmentioning
confidence: 97%
“…The apparent Km and Vm~ steady-state kinetic values for each dNTP were calculated from double-reciprocal plots of initial elongation velocity versus substrate concentrations (not shown) and are summarized in Table 1. As apparent for wild-type RT [16,19], misinsertion of the non-complementary nucleotides and subsequent extension is obtained at substantially higher nucleotide concentrations than complementary insertion of dTTP. The ratios of the insertion efficiencies for the wrong (W) versus right (R) nucleotides provide the frequency of misinsertion (Fins)…”
Section: '-Dna Misinsertion By the Mutant And Wild-type Rtsmentioning
confidence: 95%
See 1 more Smart Citation
“…Clearly, there are subtle structural features in the lentiviral RTs that make them more error prone during DNA synthesis than other RTs. Thus, the low cysteine content in both HIV-1 and HIV-2 RTs has been suggested to be associated with fidelity, since mutants lacking cysteine residues 38 and 280, or wild-type RT enzymes treated with sulfhydryl reagents, have a lower fidelity than that of the untreated wildtype enzymes [31]. It was also suggested that mutations in HIV-1 RT that confer resistance to nucleoside analogs (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…We have already suggested that the low cysteine content in HIV-1 and HIV-2 RTs might be associated with the high error proneness of these enzymes [20]. Two other mutants of HIV-1 RT resistant to nonnucleoside inhibitors, i.e.…”
mentioning
confidence: 99%